Full cost accessibility - Mengying Cui; David Levinson (Journal of Transport and Land Use)
Traditional accessibility evaluation fails to fully capture the travel costs, especially the external costs, of travel. This study develops a full cost accessibility (FCA) framework by combining the internal and external cost components of travel time, safety, emissions, and money. The example illustrated compares FCA by automobile and bicycle on a toy network to demonstrate the potential and practicality of applying the FCA framework on real networks. This method provides an efficient evaluation tool for transport planning projects.